Radiographic findings and body mass index in elderly patients with knee osteoarthritis: A cross-sectional study - Lie, Yose Steven; Kusumaningrum, Sulistyani; Budiningsih , Fatichati; Wijaya, Bayu Basuki (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2024)
Background: Osteoarthritis (OA) is a chronic condition characterized by the gradual wearing down of joint cartilage. Its prevalence is increasing due to aging populations and obesity rates. The Kellgren and Lawrence classification system is commonly used to assess OA severity based on radiologic findings.Objective: This study aims to determine the relationship between body mass index (BMI) and the radiological severity of knee OA as classified by the Kellgren and Lawrence system, in elderly patients.Methods: We conducted a cross-sectional analysis of outpatients diagnosed with knee OA at a Dr. Moewardi Regional Public Hospital from January 2020 to August 2023. Patient records and knee X-rays graded by the Kellgren and Lawrence system were reviewed. Two radiologists independently assessedthe X-rays to ensure accuracy. BMI was calculated using the formula weight (kg) divided by height (m2), with weight and height measured suing calibrated instruments. Spearman's rho bivariate correlation analysis was performed to analyze the data.Results: A total of 96 patients were analyzed, with the majority being female (62.50%) and aged 60-69 years (59.30%). The most prevalent OA severity was grade 3 (46.89%), and the most common OA location was bilateral (73.96%). There was a significant moderate correlation between Kellgren & Lawrence and BMI (p=0.000; rho=0.401).Conclusion: A moderate correlation exists between the severity of knee OA and BMI in elderly patients. Those with a higher BMI tend to present with more severe OA.